2016
DOI: 10.1177/0961463x15596703
|View full text |Cite
|
Sign up to set email alerts
|

Time for love: Partners’ time perspectives predict relationship satisfaction in romantic heterosexual couples

Abstract: The aim of the present research was to explore the role of individual differences in time perspective (TP) in predicting two relationship quality indicators: general relationship satisfaction and sexual satisfaction, in romantic heterosexual couples. A total amount of 100 dyads took part in the study. Our study revealed that relationship satisfaction indices are predicted by partners' time perspectives; both actor and partner effects proved significant. For instance, past-negative was related to lower general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 60 publications
1
13
0
1
Order By: Relevance
“…This alteration was made to simplify the interpretation results. Psychometric properties of the Polish version of the questionnaire (see Stolarski et al, 2016 ) are high (i.e., Cronbach's alpha = 0.94; correlations with intercourse frequency Spearman's rho = 0.57 for both men and women in validation studies in Poland; in the present sample, Cronbach's alpha amounted to 0.92 for men and 0.93 for women).…”
Section: Methodsmentioning
confidence: 55%
“…This alteration was made to simplify the interpretation results. Psychometric properties of the Polish version of the questionnaire (see Stolarski et al, 2016 ) are high (i.e., Cronbach's alpha = 0.94; correlations with intercourse frequency Spearman's rho = 0.57 for both men and women in validation studies in Poland; in the present sample, Cronbach's alpha amounted to 0.92 for men and 0.93 for women).…”
Section: Methodsmentioning
confidence: 55%
“…It has also been reported that higher BTP is associated with higher life satisfaction and general happiness (Barsics, Rebetez, Rochat, D'Argembeau, & Van der Linden, 2017;Boniwell & Zimbardo, 2004;Simons, Peeters, Janssens, Lataster, & Jacobs, 2016;Webster & Ma, 2013;Gao, 2011), extraversion (Stolarski, 2016;, positive orientation (Sobol-Kwapińska & Jankowski, 2016), satisfaction with interpersonal relations (Stolarski, Wojtkowska, & Kwiecińska, 2016), emotional intelligence (Stolarski, Bitner, & Zimbardo, 2011), and mindfulness (Selma & Sircova, 2013;Stolarski, Wojtkowska, & Kwiecińska, 2016). Moreover, higher BTP is negatively correlated with pathophysiological stress (Olivera-Figueroa, Juster, Morin-Major, Marin, & Lupien, 2015).…”
Section: Balanced Time Perspectivementioning
confidence: 95%
“…Biases in temporal framing have far reaching consequences for cognitive processes (Zajenkowski et al 2015), affective states (Matthews and Stolarski 2015), values and behavior in many areas (see Stolarski et al 2015a). More specifically, recent research revealed measures of TP dimensions predict variables that have been linked to aggression, including negative mood (Stolarski et al 2014;Apter et al 1990), impulsive behavior (MacKillop et al 2006;Manuck et al 1998), relationship satisfaction (Stolarski et al 2015b;Bookwala et al 1994), substance use and abuse (Keough et al 1999;Brady et al 1998), chronotype Schlarb et al 2014) and affective disorders (Gruber et al 2012;Van Praag 1986). The links between TP and behaviors which have been independently associated with aggression gives rise to a question: to what degree are the various TPs related to aggressive emotions and aggressive behavior?…”
Section: Introductionmentioning
confidence: 97%